Profil sensoris tablet effervescent kopi jahe dengan variasi konsentrasi serbuk kopi jahe dan jenis asam organik - Umar Hafidz Asy'ari Hasbullah; Marcella Berliana Purnama; Rini Umiyati; Laela Nur Rokhmah (Agroindustrial Technology, University of Trunojoyo Madura, 2023)
Ginger coffee drinks have been in great demand by consumers, and instant ginger coffee sachets have been circulating in the market. Ginger coffee effervescent tablets will be an alternative product to increase coffee consumption, and the industry can apply. This research aimed to study the sensory profile of ginger coffee effervescent tablets and their solutions made from a different concentrations of ginger coffee powder and types of organic acids. This study used a factorial design with two factors. The first factor was the concentration of 30 % and 50 % of ginger coffee powder. The second factor was the type of organic acid which consists of tartaric acid, malic acid, and a combination of both acids. A descriptive sensory test was conducted by using trained panelists. The results showed that the increasing concentration of ginger coffee powder in the formulation had a significant effect on the sensory profile of the ginger coffee tablet and effervescent solution, especially the darker and browner colors. In contrast, the taste and aroma weren’t changed significantly. The difference in organic acids in the formulation did not cause significant differences in the sensory profile of the ginger coffee effervescent solution and tablets. In general, the dissolution of tablets in water into an effervescent solution will increase the color sensory profile but not the aroma profile.